Optimising an archer`s foot position to obtain a competitive advantage - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
The World Archery shooting rules provide some latitude in relation to an archer`s position on the shooting line. This means that the archer could stand at different distances from the target, while still meeting competition regulations. One would think that standing closer to the target should be an advantage; however, most archers do not take this approach. This article considers the score increase that may be attributable to standing in the optimum position, which can lead to a potential higher ranking place at major international indoor and outdoor archery competitions.